Monitoring And Evaluation Information Technology Competence And Basic Communication Administration Of Students UIN Kiai Haji Achmad Siddiq Jember - Dani Hermawan; Diah Novita Sari (JIEMAN: Journal of Islamic Educational Management, 2023)
This article aims to explain the results and impact of monitoring and evaluation of Basic Administrative Information and Communication Technology competencies in Islamic Education Management Students in the 2019-2021 class, such as Microsoft word, Microsoft excel and Internet Digitalization. The method used is a descriptive quantitative method. Collecting data using tests, interviews and documentation. Data analysis used descriptive statistical analysis using the Statistical Package for the Social Sciences (SPSS) for windows version 22. The results of the analysis showed that most of the implementation of Basic Information Technology and Computer (ICT) Administration competencies in MPI students for the 2019-2021 class year had not been carried out in accordance with applicable vision and mission provisions. There are several dominant factors that cause this; lack of computer learning, especially on Microsoft Excel in preparing the administration of facilities and infrastructure, and its completeness. However, after knowing the basic administrative ICT scores that have been filled in the tests given by researchers, students want to change their mindset by improving themselves with basic computer administration courses according to the total score of 91.8%. Artikel ini bertujuan untuk menjelaskan tentang hasil dan dampak monitoring dan evaluasi kompetensi Teknologi Informasi dan Komunikasi Dasar Administrasi Pada Mahasiswa Manajemen Pendidikan Islam Tahun angkatan 2019-2021 seperti halnya Microsoft word, Microsoft excel dan Digitaliasai Internet. Metode yang digunakan adalah metode kuantitatif deskriptif. Pengumpulan data menggunakan tes, wawancara dan dokumentasi. Analisis data menggunakan analisis statistic deskriptif menggunakan Statistical Package for the Social Sciences (SPSS) for windows version 22. Hasil analiasis menunjukkan bahwa sebagian besar pelaksanaan kompetensi Teknologi Informasi dan Komputer (TIK) Dasar Administrasi pada mahasiswa MPI tahun angkatan 2019-2021 belum terlaksana sesuai dengan ketentuan visi dan misi yang berlaku. Ada beberapa faktor dominan yang menyebabkan hal tersebut; kurangnya belajar komputer terutama pada Microsoft excel dalam menyusun administrasi sarana dan prasarana, dan kelengkapannya. Namun setelah mengetahui nilai TIK dasar administrasi yang sudah diisi dalam tes yang di berikan oleh peneliti mahasiswa ingin merubah pola pikirnya dengan memperbaiki diri dengan kursus komputer dasar administrasi sesuai dengan jumlah perolehan skor 91,8%.